2013
DOI: 10.1021/ar400156z
|View full text |Cite
|
Sign up to set email alerts
|

Endohedral Metallofullerenes Based on Spherical Ih-C80 Cage: Molecular Structures and Paramagnetic Properties

Abstract: Fullerenes are carbon cages assembled from fused hexagons andpentagons that have closed networks and conjugated π systems. The curve of the fullerene structure requires that the constituent carbon atoms take on a pyramidal shape and produces extra strain energy. However, the highly symmetrical geometry of the fullerene decreases the surface tension in these structures, so highly symmetrical fullerenes are usually very stable. For example, C60 with icosahedral symmetry (Ih) is the most stable fullerene molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
108
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 64 publications
6
108
0
Order By: Relevance
“…To date, more than two hundred EMFs have been characterized, including mono-metallofullerenes, dimetallofullerenes, trimetallofullerenes, and fullerenes incorporating clusters various kinds [4]. Amongst the EMFs, those in which the encapsuland is a metallic cluster have attracted attention because of their novel geometries and properties [5,6]. However, as far as we are aware, the mechanism of formation of EMFs has not yet been clarified, even though so many EMFs have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…To date, more than two hundred EMFs have been characterized, including mono-metallofullerenes, dimetallofullerenes, trimetallofullerenes, and fullerenes incorporating clusters various kinds [4]. Amongst the EMFs, those in which the encapsuland is a metallic cluster have attracted attention because of their novel geometries and properties [5,6]. However, as far as we are aware, the mechanism of formation of EMFs has not yet been clarified, even though so many EMFs have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] Since the discovery of Sc 3 N@C 80 in 1999, [10] cluster fullerenes (CFs) have been of particular interest in the field of endohedral fullerenes as ar esult of their exceptionally high yield and excellent stabilitya nd the unique structural variety of both clusters and cages, which resultsi nt heir tunable physical and chemical properties. [11][12][13][14] To date,avariety of cluster fullerenes have been reported, including nitride (NCFs), [15][16][17] carbide( CCFs), [18,19] hydrocarbide (HCCFs), [20] oxide (OCFs), [21,22] sulfide( SCFs), [23][24][25] carbonnitride (CNCFs), [26,27] and di/trimetallic clusterf ullerenes. [28,29] In particular,t he OCF family has demonstratede xceptional structuralv ersatility of the encapsulated oxide clusters, whichh ave includedS c 2 O, [21] Sc 4 O 2 , [22] and Sc 4 O 3 [30] structures.I ncontrast, the reported cage structures of this family have been limited to I h (7)-C 80 , C s (6)-C 82 ,a nd the very recent C 2 (7892)-C 70 cages.…”
Section: Introductionmentioning
confidence: 99%
“…9 For example, isomeric cages of C 80 are popular cages for various forms of endohedral fullerenes. 21 However, one of them, C 2v (5)-C 80 , remained missing until its recent discovery by Akasaka et al in the study of Sc 2 C 2 @ C 2v (5)-C 80 . 22 It was found that this cage structure was stabilized by a four-electron-transfer from the encapsulated Sc 2 C 2 cluster.…”
Section: ■ Introductionmentioning
confidence: 99%